Development of PID Controller for Controlling Desired Level of Coupled Tank System - Jaafar, Hazriq Izzuan; Syed Hussien, Sharifah Yuslinda; Selamat, Nur Asmiza; Mohd Aras, Mohd Shahrieel; Ab Rashid, Mohd Zamzuri (Blue Eyes Intelligence Engineering & Sciences Publication Pvt. Ltd., 2014)
The industrial application of Coupled Tank System(CTS) are widely used especially in chemical process industries. The overall process need liquids to be pumped, stored in the tank and pumped again to another tank for certain desired level. Nevertheless, the level of liquid in tank need to be controlled and flow between two tanks must be regulated. This paper presents development of Proportional-Integral-Derivative (PID) controller for controlling the desired liquid level of the CTS. Various conventional techniques of PID tuning method will be tested in order to obtain the PID controller parameters. Simulation is conducted within MATLAB environment to verify the performances of the system in terms of Rise Time (Ts), Settling Time (Ts), Steady State Error (SSE) and Overshoot(OS). Four techniques which are trial and error method, auto-tuning method, Ziegler-Nichols (Z-N) method and Cohen-Coon (C-C) method will be implemented and all the performance results will be analyzed. It has been demonstrated that performances of CTS can be improved with appropriate technique of PID tuning methods.